Coupling Resonances of Surface Plasmon in Gold Nanorod/Copper Chalcogenide Core−Shell Nanostructures and Their Enhanced Photothermal Effect. Issue 15 (4th June 2018) - Li, Yingying; Pan, Guiming; Liu, Qiyu; Ma, Liang; Xie, Ying; Zhou, Li; Hao, Zhonghua; Wang, Ququan
Abstract: Dual plasmonic Au@Cu2−x S core−shell nanorods (NRs) have been fabricated by using a hydrothermal method and plasmon‐coupled effect between the Au core and Cu2−x S shell in the near‐infrared (NIR) region. The extinction spectrum of Au@Cu2−x S NRs is dominated by the surface plasmon resonance (SPR) of the Cu2−x S shell, the transverse surface plasmon resonance (TSPR), and the longitudinal surface plasmon resonance (LSPR) of the Au NRs. With the Cu2−x S shell increasing (fixed Au NRs), the TSPR peak slightly redshifts and the LSPR and SPR peaks blueshift, owing to competition between the redshift of the refractive index effect and blueshift from the plasmon coupled effect. Although, for Au@Cu2 S NRs, only TSPR and LSPR peaks can be seen and a redshift arises with the increasing Cu2 S shell thickness, implying that no plasmonic coupling between Au NRs and Cu2 S shell occurred. The extinction spectrum of the Au@Cu2−x S NRs with three coupled resonance peaks is simulated by using the FDTD method, taking into account the electron‐transfer effect. The dispersion properties of the coupling of Au@Cu2−x S NRs with the LSPR of the initial Au core are studied experimentally by changing the length of the Au NRs, which are explained theoretically by the coupled harmonic oscillator model. The calculated coupled coefficients between SPR of the Cu2−x S shell and LSPR of the Au NRs is 180 meV, which is much stronger than that of TSPR of Au NRs of 55 meV. Finally, the enhanced photothermal effect of Au@Cu2−x S NRs has been demonstrated. Abstract : Couple up: The plasmon coupling resonance of Au@Cu2−x S nanocrystals is investigated and coupling coefficients between the Au nanoroads and Cu2−x S shell are calcualted.